Search for supersymmetry in events with large missing transverse momentum, jets, and at least one tau lepton in 7 TeV proton-proton collision data with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2012)
A search for supersymmetry (SUSY) in events with large missing transverse momentum, jets, and at least one hadronically decaying τ lepton, with zero or one additional light lepton (e/μ), has been performed using 4. 7 fb-1 of proton-proton collision data at √s=7 TeV recorded with the ATLAS detector at the Large Hadron Collider. No excess above the Standard Model background expectation is observed and a 95 % confidence level visible cross-section upper limit for new phenomena is set. In the framework of gauge-mediated SUSY-breaking models, lower limits on the mass scale Λ are set at 54 TeV in the regions where the τ1 is the next-to-lightest SUSY particle (tanβ>20). These limits provide the most stringent tests to date of GMSB models in a large part of the parameter space considered. © 2012 CERN for the benefit of the ATLAS collaboration.